Inhibition of cyclic GMP-dependent protein kinase-mediated effects by (Rp)-8-bromo-PET-cyclic GMPS. - Butt, E. (1995)
1. The modulation of the guanosine 3':5'-cyclic monophosphate (cyclic GMP)- and adenosine 3':5'-cyclic monophosphate (cyclic AMP)-dependent protein kinase activities by the diastereomers of 8-bromo-beta phenyl-1, N2-ethenoguanosine 3':5'-cyclic monophosphorothioate, ((Rp)- and (Sp)-8-bromo-PET-cyclic GMPS) was investigated by use of purified protein kinases. In addition, the effects of (Rp)-8-bromo-PET-cyclic GMPS on protein phosphorylation in intact human platelets and on [3H]-noradrenaline release and neurogenic vasoconstriction in electrical field stimulated rat tail arteries were also studied. 2. Kinetic analysis with purified cyclic GMP-dependent protein kinase (PKG) type I alpha and I beta, which are expressed in the rat tail artery, revealed that (Rp)-8-bromo-PET-cyclic GMPS is a competitive inhibitor with an apparent Ki of 0.03 microM. The activation of purified cyclic AMP-dependent protein kinase (PKA) type II was antagonized with an apparent Ki of 10 microM. 3. In human platelets, (Rp)-8-bromo-PET-cyclic GMPS (0.1 mM) antagonized the activation of the PKG by the selective activator 8-(4-chlorophenylthio)-guanosine 3':5'-cyclic monophosphate (8-pCPT-cyclic GMP; 0.2 mM) without affecting the activation of PKA by (Sp)-5, 6-dichloro-1-beta-D-ribofurano-sylbenzimidazole- 3':5'-cyclic monophosphorothioate ((Sp)-5,6-DCl-cyclic BiMPS; 0.1 mM). 4. (Rp)-8-bromo-PET-cyclic GMPS was not hydrolysed by the cyclic GMP specific phosphodiesterase (PDE) type V from bovine aorta but potently inhibited this PDE. 5. The corresponding sulphur free cyclic nucleotide of the two studied phosphorothioate derivatives, 8-bromo-beta-phenyl-1, N2-ethenoguanosine-3':5'-cyclic monophosphate (8-bromo-PET-cyclic GMP), had no effect on electrically-induced [3H]-noradrenaline release but concentration-dependently decreased the stimulation-induced vasoconstriction. (Rp)-8-bromo-PET-cyclic GMPS (3 microM) shifted the vasoconstriction response to the right without affecting stimulation evoked tritium overflow. 6. The NO donor, 3-morpholinosydnonimine (SIN-1) relaxed rat tail arteries precontracted with phenylephrine (1 microM). The SIN-1 concentration-relaxation curve was shifted in a parallel manner to the right by (Rp)-8-bromo-PET-cyclic GMPS, suggesting that the relaxation was mediated by a cyclic GMP/PKG-dependent mechanism. 7. The [3H]-noradrenaline release-enhancing effect and stimulation-induced decrease in vasoconstriction of forskolin were unaffected by (Rp)-8-bromo-PET-cyclic GMPS. Moreover, the forskolin concentration-relaxation curve was not changed in the presence of the PKG inhibitor, suggesting a high selectivity in intact cells for PKG- over PKA-mediated effects. 8. The results obtained indicate that (Rp)-8-bromo-PET-cyclic GMPS presently is the most potent and selective inhibitor of PKG and is helpful in distinguishing between cyclic GMP and cyclic AMP messenger pathways activation. Therefore, this phosphorothioate stereomer may be a useful tool for studying the role of cyclic GMP in vitro.